Use of Carotenogenic Neurospora in Fermentation of Agricultural Byproduct for Poultry Feed - Nurfaizin .; P R Matitaputty (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Agricultural byproduct is biomass that potential to partly subtitute the conventional feed. However, there are some constraints such as high fiber, low protein and carotene contents. One of the efforts to improve the nutritive value of agricultural byproduct is fermentation using carotenogenic Neurospora. This fungi easily and readily grows on substrate fermented in aerobic condition. Neurospora fermentation is able to reduce crude fiber, to increase crude protein and carotene content of substrate. Utilization of Neurospora fermented product as poultry feed ingredients increased productivity and product quality more efficiently.